Skeleton extraction and pruning point identification of jujube tree for dormant pruning using space colonization algorithm - Fu, Yuxing; Xia, Yuyang; Zhang, Huiming; Fu, Meng; Wang, Yong; Fu, Wei; Shen, Congju (Frontiers in Plant Science, 2023)
The dormant pruning of jujube is a labor-intensive and time-consuming activities in the production and management of jujube orchard, which mainly depends on manual operation. Automated pruning using robots could be a better way to solve the shortage of skilled labor and improve efficiency. In order to realize automatic pruning of jujube tree, a method of pruning point identification based on skeleton information is presented. This study used RGB-D camera to collect multi-view information of jujube tree, and built a complete point cloud information model of jujube tree. Space colonization algorithm acts on the global point cloud to generate the skeleton of jujube tree. The iterative relationship between skeleton points was represented by constructing a directed graph. The proposed skeleton analysis algorithm marked skeleton as the trunk, the primary branches and the lateral branches, and identified the pruning points under the guidance of pruning rules. Finally, the visual model of the pruned jujube tree was established through the skeleton information. The results showed that the registration errors of individual jujube trees were less than 0.91 cm, and the average registration error was 0.66 cm, which provided a favourable data base for skeleton extraction. The skeleton structure extracted by the spatial colonization algorithm had a high degree of coincidence with the jujube tree, and the identified pruning points were all located on the primary branches of the jujube tree. The study provides a method to identify the pruning points of jujube trees, and successfully verifies the validity of the pruning points, which can provide a reference for the location of the pruning points and visual research basis for automatic pruning.